Audio-visual teaching methods in learning art education skills for preparatory stage students (Journal of Humanities and Social Sciences Research, 2023)
The study aimed to find the most effective educational approaches for teaching and learning art education abilities for students at the preparatory level. To do this, a sample of (60) male and female students from schools in Hilla (10-12) years old were separated into three groups: the visual learning group, the verbal learning group, and the verbal learning group. Group for verbal and visual learning. Each group consists of (20) male and female students who have been taught many skills over a three-week period utilizing one of the three teaching approaches. Arithmetic means and standard deviations, as well as one-way ANOVA and Scheffe's test, were used for comparison between groups. The results of the study showed the effectiveness of each method and its importance in student acquisition and learning. The effectiveness of the verbal and visual learning method when teaching motor skills is compared to other teaching methods. The researcher recommended several recommendations, the most significant being the use of mixed methods (visual and verbal) in teaching drawing skills to beginners.